Granules containing composite fibers composed of fibers and inorganic particles

By controlling the moisture content and surface coating of composite fibers in granules, the flowability and dispersibility of granules containing composite fibers and inorganic particles are significantly improved, enabling effective blending and functional enhancement.

JP2025038110AActive Publication Date: 2025-03-18NIPPON PAPER IND CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024220586
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-20
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
2040-09-15

AI Technical Summary

Technical Problem

Existing granules containing composite fibers and inorganic particles lack excellent flowability, making them difficult to blend into other products effectively.

Method used

The production of granules with controlled moisture content, specifically between 0.1 to 10 mm in particle size and less than 60% water content, along with the use of composite fibers where at least 15% of the fiber surface is coated with inorganic particles, enhances their flowability and dispersibility.

Benefits of technology

The resulting granules exhibit improved fluidity and dispersibility, allowing for easier blending into other products and imparting functionalities such as deodorizing effects based on the properties of the inorganic particles used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038110000003
    Figure 2025038110000003
  • Figure 2025038110000004
    Figure 2025038110000004
  • Figure 2025038110000005
    Figure 2025038110000005
Patent Text Reader

Abstract

To provide highly flowable granules comprising a complex fiber of a fiber with inorganic particles.SOLUTION: Granules comprising a complex fiber of a fiber with inorganic particles are provided herein. The inventive granules have a particle size of 0.1 to 10 mm and a water content of less than 60%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to granules containing composite fibers of fibers and inorganic particles, and a method for producing the same. [Background technology]

[0002] Composite fibers with various properties have been developed by attaching inorganic particles to the fiber surface. For example, it is known that inorganic particles can be attached to the fiber surface by synthesizing inorganic substances in the presence of fibers.

[0003] For example, composite fibers of calcium carbonate and fiber (Patent Document 1), composite fibers of magnesium carbonate and fiber (Patent Document 2), composite fibers of calcium phosphate and fiber (Patent Document 3), composite fibers of hydrotalcite and fiber (Patent Document 4), and composite fibers of silica / alumina and fiber (Patent Document 5) are known.

[0004] Additionally, composite fibers in which most of the fiber surface is covered with inorganic particles (Patent Document 6) and composite fibers in which inorganic particles are attached to the fiber surface to improve flame retardancy (Patent Document 7) have also been reported. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication WO2015 / 152283 [Patent Document 2] International Publication WO2017 / 043580 [Patent Document 3] International Publication WO2017 / 043585 [Patent Document 4] International Publication WO2018 / 030521 [Patent Document 5] International Publication WO2019 / 163659 [Patent Document 6] International Publication WO2017 / 057154 [Patent Document 7] International Publication WO2019 / 159943 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide granules which contain composite fibers of fibers and inorganic particles and have excellent flowability. [Means for solving the problem]

[0007] As a result of extensive research into the above problems, the present inventors have discovered that excellent granules can be obtained by controlling the moisture content before and during granulation, and have thus completed the present invention.

[0008] That is, the present invention includes the following aspects, but is not limited thereto. [1] Granules containing a composite fiber of fiber and inorganic particles, with a particle size of 0.1 to 10 mm and a moisture content of less than 60%. [2] The granules described in [1], having an angle of repose of 30 to 58°. [3] The granules according to [1] or [2], wherein the inorganic particles include metal salts of calcium, magnesium, barium or aluminum, metal particles including titanium, copper or zinc, or silicates. [4] Granules according to any one of [1] to [3], wherein the inorganic particles are hydrotalcite. [5] Granules according to any one of [1] to [4], wherein the weight ratio of inorganic particles in the granules is 10% or more. [6] The granules according to any one of [1] to [5], wherein the fibers are cellulose fibers. [7] Granules according to any one of [1] to [6], in which 15% or more of the fiber surface is covered with inorganic particles. [8] A method for producing granules according to any one of [1] to [7], comprising the steps of: synthesizing inorganic particles in a liquid containing fibers to obtain composite fibers; and granulating the composite fibers to produce granules having a particle size of 0.1 to 10 mm. [9] The method according to [8], wherein in the granulation step, the composite fiber is granulated while being dried.

[10] The method according to [8], wherein the moisture content of the composite fiber is reduced to less than 60% before granulation.

[11] The method according to [8], in which the composite fibers are finely milled and then granulated. Effect of the Invention

[0009] According to the present invention, granules can be obtained by processing composite fibers of fibers and inorganic particles into granules. The obtained granules have excellent fluidity and dispersibility, so they can be easily blended with other products to impart functionality to other products according to the characteristics of the inorganic particles. In particular, when inorganic particles with a high deodorizing effect are used, granules with a high deodorizing effect can be obtained. In addition, by using composite fibers of fibers and inorganic particles as the raw material for the granules, functionality according to the characteristics of the inorganic particles can be imparted while suppressing the blending amount of the inorganic particles. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram of the production apparatus used in Experiment 1 (P: pump). [Diagram 2] Electron microscope photograph of sample a (magnification: 3000x). [Diagram 3] Electron microscope photograph of sample b (magnification: 3000x). [Figure 4] Electron microscope photograph of sample c (magnification: 3000 times). [Diagram 5] Electron microscope photograph of sample d (magnification: 3000x). [Figure 6] Electron microscope photograph of sample f (magnification: 3000x). [Figure 7] 1 is a photograph showing the appearance of Sample 1 in Experiment 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention relates to granules containing composite fibers of fibers and inorganic particles. Granules generally refer to particles with a particle size larger than that of powder, and have a particle size of 0.1 mm or more. The composite fiber granules of the present invention can be obtained, for example, by solidifying powder and forming it into slightly large particles, and the moisture content (solid content) may be adjusted by drying or adding water as necessary. Composite fibers of fibers and inorganic particles may be obtained in a state with a high moisture content, in which case the composite fibers may be dried and formed into slightly large particles to produce the granules. Granules have the advantage that they are less likely to generate dust or to coagulate and hinder dissolution when water is added, as is the case with powders, and can be easily dispersed in other products compared to composite fibers in the form of aqueous suspensions or pulps.

[0012] There is no particular restriction on the dryer used for drying the composite fiber of the synthesized fiber and inorganic particles, but for example, a flash dryer, band dryer, spray dryer, vacuum dryer, low-temperature dryer, rotary dryer, Plosser mixer, oven, etc. can be suitably used. Among these, it is preferable to use a device capable of performing drying and granulation in parallel, such as a Plosser mixer, because this makes it easy to produce granules of the desired particle size from the composite fiber. In the present invention, the composite fiber may be pulverized before being granulated.

[0013] Water can be added by dripping from a dedicated pipe or a line installed as necessary. The liquid to be added can be water (industrial water, tap water, distilled water, ultrapure water), a solution containing metal ions, a dispersion of starch or CMC, or a solution containing anionic, cationic, or nonionic chemicals, and can be adjusted as appropriate for the purpose.

[0014] In the present invention, the particle size of the granules is 0.1 mm or more and 10 mm or less. The particle size of the granules is preferably 0.2 mm or more and 4 mm or less, more preferably 0.3 mm or more and 3 mm or less, and the particle size of the granules can be 0.5 mm or more and 2 mm or less. If the particle size is too small, the granules tend to scatter, and if the particle size is too large, they are difficult to disperse when mixed with other raw materials.

[0015] The moisture content (moisture concentration) before granulation can be, for example, 0 to 80%, preferably 2 to 70%, more preferably 4 to 60%, and particularly preferably 6 to 50%. If the moisture content before granulation is too high, drying takes a long time and efficiency decreases, while if the moisture content before granulation is too low, it may be difficult to uniformly disperse the raw material depending on the device used to process the granules, so a moderate moisture content is more suitable for the production of granules.

[0016] The moisture content of the granules according to the present invention is less than 60%, and in a preferred embodiment, the moisture content of the granules is less than 45%, and may be less than 30%. By reducing the moisture content of the granules, the flowability of the granules can be improved.

[0017] The granules according to the present invention have excellent fluidity and are easy to handle. In a preferred embodiment, the angle of repose of the granules according to the present invention is 30 to 58°, more preferably 32 to 50°, and particularly preferably 34 to 40°. Granules having a small angle of repose can be obtained by lowering the moisture content of the granules or adjusting the particle size of the granules.

[0018] Synthesis of composite fibers In the present invention, composite fibers can be synthesized by synthesizing inorganic particles in a solution containing fibers such as cellulose fibers. This is because the fiber surface is a suitable site for the precipitation of inorganic particles, making it easy to synthesize composite fibers. As a method for synthesizing composite fibers, for example, a solution containing fibers and precursors of inorganic particles may be stirred and mixed in an open reaction tank to synthesize a composite, or an aqueous suspension containing fibers and precursors of inorganic particles may be injected into a reaction vessel. As will be described later, when an aqueous suspension of inorganic precursors is injected into a reaction vessel, cavitation bubbles may be generated, and inorganic particles may be synthesized in the presence of the cavitation bubbles. The inorganic particles can be synthesized on the cellulose fibers by known reactions.

[0019] It is generally known that inorganic particles are generated through a process of clustering (repeatedly gathering and dispersing at a stage where the number of atoms and molecules gathered is small), nucleation (transitioning from clusters to a stable aggregated state, and when the size exceeds a critical point, the captured atoms and molecules do not disperse), and growth (new atoms and molecules gather at the nuclei and the particles become larger), and it is said that the higher the raw material concentration and reaction temperature, the easier nucleation occurs. The composite fiber of the present invention can be obtained by efficiently bonding nuclei to the fibers and promoting particle growth by adjusting mainly the raw material concentration, the beating degree (specific surface area) of the pulp, the viscosity of the solution containing the fibers, the concentration and addition speed of the additive chemicals, the reaction temperature, and the stirring speed, thereby obtaining composite fibers in which the surfaces of cellulose fibers are tightly coated with inorganic particles.

[0020] In the present invention, the liquid may be injected under conditions that generate cavitation bubbles in the reaction vessel, or under conditions that do not generate cavitation bubbles. In either case, the reaction vessel is preferably a pressure vessel. Note that the pressure vessel in the present invention refers to a vessel to which a pressure of 0.005 MPa or more can be applied. In the case of conditions that do not generate cavitation bubbles, the pressure in the pressure vessel is preferably 0.005 MPa or more and 0.9 MPa or less in terms of static pressure.

[0021] (Cavitation bubbles) When synthesizing the composite fiber according to the present invention, inorganic particles can be precipitated in the presence of cavitation bubbles. In the present invention, cavitation is a physical phenomenon in which bubbles appear and disappear in a short time due to pressure differences in a fluid flow, and is also called a cavity phenomenon. Bubbles generated by cavitation (cavitation bubbles) are generated from very small "bubble nuclei" of 100 microns or less that exist in the liquid when the pressure in the fluid becomes lower than the saturated vapor pressure for a very short time.

[0022] In the present invention, cavitation bubbles can be generated in a reaction vessel by a known method, such as generating cavitation bubbles by injecting a fluid at high pressure, generating cavitation by stirring the fluid at high speed, generating cavitation by causing an explosion in the fluid, or generating cavitation by an ultrasonic vibrator (vibratory cavitation).

[0023] In the present invention, cavitation can be generated by using the reaction solution such as the raw material as the injection liquid as it is, or cavitation bubbles can be generated by injecting some kind of fluid into the reaction vessel. The fluid forming the liquid jet may be any liquid, gas, or solid such as powder or pulp, as long as it is in a flowing state, or may be a mixture of these. Furthermore, if necessary, another fluid such as carbon dioxide gas can be added as a new fluid to the above fluid. The above fluid and the new fluid may be injected after being mixed uniformly, or may be injected separately.

[0024] A liquid jet is a jet of liquid or a fluid in which solid particles or gas are dispersed or mixed in a liquid, and refers to a liquid jet containing raw material slurry of pulp or inorganic particles or air bubbles. The air referred to here may include air bubbles caused by cavitation.

[0025] Cavitation occurs when a liquid is accelerated and the local pressure becomes lower than the vapor pressure of the liquid, so the flow rate and pressure are particularly important. For this reason, the cavitation number σ, a basic dimensionless number that represents the cavitation state, is desirably 0.001 to 0.5, preferably 0.003 to 0.2, and particularly preferably 0.01 to 0.1. If the cavitation number σ is less than 0.001, the effect is small because the pressure difference with the surroundings when the cavitation bubbles collapse is low, and if it is greater than 0.5, the pressure difference in the flow is low and cavitation is less likely to occur.

[0026] In addition, when generating cavitation by injecting the injection liquid through a nozzle or an orifice pipe, the pressure of the injection liquid (upstream pressure) is desirably 0.01 MPa or more and 30 MPa or less, preferably 0.7 MPa or more and 20 MPa or less, and more preferably 2 MPa or more and 15 MPa or less. If the upstream pressure is less than 0.01 MPa, it is difficult to generate a pressure difference with the downstream pressure, and the effect is small. Furthermore, if it is higher than 30 MPa, a special pump and pressure vessel are required, and energy consumption increases, which is disadvantageous in terms of cost. On the other hand, the pressure inside the vessel (downstream pressure) is preferably 0.005 MPa or more and 0.9 MPa or less in terms of static pressure. Furthermore, the ratio of the pressure inside the vessel to the pressure of the injection liquid is preferably in the range of 0.001 to 0.5.

[0027] In the present invention, inorganic particles can be synthesized by injecting the injection liquid under conditions that do not generate cavitation bubbles. Specifically, the pressure of the injection liquid (upstream pressure) is set to 2 MPa or less, preferably 1 MPa or less, and the pressure of the injection liquid (downstream pressure) is released and more preferably set to 0.05 MPa or less.

[0028] The jet speed of the jet of the injected liquid is preferably in the range of 1 m / s to 200 m / s, and more preferably in the range of 20 m / s to 100 m / s. If the jet speed is less than 1 m / s, the pressure drop is low and cavitation is unlikely to occur, so the effect is weak. On the other hand, if the jet speed is more than 200 m / s, high pressure and special equipment are required, which is cost-inefficient.

[0029] In the present invention, cavitation may be generated in a reaction vessel in which inorganic particles are synthesized. It is possible to perform the process in one pass, but it is also possible to circulate the process as many times as necessary. Furthermore, it is possible to perform the process in parallel or in series using a plurality of generating means.

[0030] The injection of liquid to generate cavitation may be done in a vessel open to the atmosphere, but is preferably done in a pressurized vessel to control the cavitation.

[0031] When cavitation is generated by liquid injection, the solids concentration of the reaction solution is preferably 30% by weight or less, more preferably 20% by weight or less. This is because such a concentration makes it easier for cavitation bubbles to act uniformly on the reaction system. In addition, from the viewpoint of reaction efficiency, the aqueous suspension of slaked lime, which is the reaction solution, preferably has a solids concentration of 0.1% by weight or more.

[0032] In the present invention, for example, when synthesizing a composite of calcium carbonate and cellulose fiber, the pH of the reaction solution is basic at the start of the reaction but changes to neutral as the carbonation reaction proceeds. Therefore, the reaction can be controlled by monitoring the pH of the reaction solution.

[0033] In the present invention, by increasing the injection pressure of the liquid, the flow rate of the injected liquid increases, and the pressure decreases accordingly, so that stronger cavitation can be generated. In addition, by increasing the pressure in the reaction vessel, the pressure in the region where the cavitation bubbles collapse increases, and the pressure difference between the bubbles and the surroundings increases, so that the bubbles collapse violently and the impact force can be increased. Furthermore, dissolution and dispersion of the carbon dioxide gas introduced can be promoted. The reaction temperature is preferably 0°C or higher and 90°C or lower, and particularly preferably 10°C or higher and 60°C or lower. In general, since the impact force is thought to be maximum at the midpoint between the melting point and the boiling point, about 50°C is suitable for an aqueous solution, but even if the temperature is lower than that, it is not affected by the vapor pressure, so a high effect can be obtained within the above range.

[0034] When producing the composite fiber of the present invention, various known auxiliary agents can be further added. For example, a chelating agent can be added, and specific examples thereof include polyhydroxycarboxylic acids such as citric acid, malic acid, and tartaric acid, dicarboxylic acids such as oxalic acid, sugar acids such as gluconic acid, aminopolycarboxylic acids such as iminodiacetic acid and ethylenediaminetetraacetic acid, and alkali metal salts thereof, alkali metal salts of polyphosphoric acids such as hexametaphosphoric acid and tripolyphosphoric acid, amino acids such as glutamic acid and aspartic acid, and alkali metal salts thereof, ketones such as acetylacetone, methyl acetoacetate, and allyl acetoacetate, sugars such as sucrose, and polyols such as sorbitol. In addition, as a surface treatment agent, saturated fatty acids such as palmitic acid and stearic acid, unsaturated fatty acids such as oleic acid and linoleic acid, alicyclic carboxylic acids, resin acids such as abietic acid, their salts, esters and ethers, alcohol-based surfactants, sorbitan fatty acid esters, amide-based and amine-based surfactants, polyoxyalkylene alkyl ethers, polyoxyethylene nonylphenyl ether, sodium alpha-olefin sulfonate, long-chain alkyl amino acids, amine oxides, alkylamines, quaternary ammonium salts, aminocarboxylic acids, phosphonic acids, polyvalent carboxylic acids, condensed phosphoric acids, etc. can be added. In addition, a dispersant can be used as necessary. Examples of the dispersant include sodium polyacrylate, sucrose fatty acid esters, glycerin fatty acid esters, acrylic acid-maleic acid copolymer ammonium salts, methacrylic acid-naphthoxy polyethylene glycol acrylate copolymers, methacrylic acid-polyethylene glycol monomethacrylate copolymer ammonium salts, polyethylene glycol monoacrylate, etc. These can be used alone or in combination. In addition, the timing of addition may be before or after the synthesis reaction. Such additives can be added in an amount of preferably 0.001 to 20%, more preferably 0.1 to 10%, based on the inorganic particles. In addition, in the present invention, the reaction can be a batch reaction or a continuous reaction. In general, it is preferable to carry out a batch reaction process because of the convenience of discharging the residue after the reaction.The scale of the reaction is not particularly limited, and the reaction may be performed on a scale of 100 L or less, or on a scale of more than 100 L. The size of the reaction vessel may be, for example, about 10 L to 100 L, or about 100 L to 1000 L.

[0035] The reaction can also be controlled by adjusting the electrical conductivity of the reaction solution or the reaction time, specifically, by adjusting the residence time of the reactants in the reaction tank. In addition, in the present invention, the reaction can also be controlled by stirring the reaction solution in the reaction tank or by carrying out a multi-stage reaction.

[0036] In the present invention, the composite fiber, which is the reaction product, is obtained as a suspension, and therefore, if necessary, it can be stored in a storage tank, or can be subjected to treatments such as concentration, dehydration, pulverization, classification, aging, and dispersion. These can be performed by known processes, and can be appropriately determined in consideration of the application, energy efficiency, and the like. For example, the concentration and dehydration treatments are performed using a centrifugal dehydrator, a sedimentation concentrator, and the like. Examples of this centrifugal dehydrator include a decanter and a screw decanter. There is no particular limitation on the type of filter or dehydrator used, and general ones can be used, but for example, a pressurized dehydrator such as a filter press, a drum filter, a belt press, or a tube press, or a vacuum drum dehydrator such as an Oliver filter can be suitably used to produce a calcium carbonate cake. Examples of the grinding method include a ball mill, a sand grinder mill, an impact mill, a high-pressure homogenizer, a low-pressure homogenizer, a dyno mill, an ultrasonic mill, a kanda grinder, an attritor, a stone mill, a vibration mill, a cutter mill, a jet mill, a disintegrator, a beater, a single-screw extruder, a twin-screw extruder, an ultrasonic agitator, a household juicer mixer, etc. Examples of the classification method include a sieve such as a mesh, an outward or inward slit or round-hole screen, a vibration screen, a heavy foreign matter cleaner, a light foreign matter cleaner, a reverse cleaner, a sieving tester, etc. Examples of the dispersion method include a high-speed disperser, a low-speed kneader, etc.

[0037] The composite fiber of the present invention can be blended with a filler or pigment in the form of a suspension without being completely dehydrated, or can be dried to form a powder. There are no particular limitations on the dryer used in this case, and for example, a flash dryer, band dryer, spray dryer, etc. can be suitably used.

[0038] The composite fiber of the present invention can be modified by known methods. For example, in one embodiment, the surface can be made hydrophobic to enhance compatibility with resins, etc.

[0039] In the present invention, water is used for preparing the suspension, etc. As the water, ordinary tap water, industrial water, groundwater, well water, etc. can be used. In addition, ion-exchanged water, distilled water, ultrapure water, industrial wastewater, and water obtained during separation and dehydration of a reaction solution can also be suitably used.

[0040] In the present invention, the reaction solution in the reaction tank can be circulated. By circulating the reaction solution in this way and promoting stirring of the solution, the reaction efficiency can be increased and the desired composite of inorganic particles and fibers can be easily obtained.

[0041] inorganic particles In the present invention, the inorganic particles to be composited with the fibers are not particularly limited, but are preferably inorganic particles that are insoluble or poorly soluble in water. Since the synthesis of the inorganic particles may be performed in an aqueous system, and the fiber composite may be used in an aqueous system, it is preferable that the inorganic particles are insoluble or poorly soluble in water.

[0042] The inorganic particles referred to here are compounds of metal elements or nonmetal elements. Compounds of metal elements are compounds of metal cations (e.g., Na + , Ca 2+ , Mg 2+ , Al 3+ , B.A. 2+ ) and anions (e.g., O 2- , O.H. - , CO3 2- , PO4 3- , SO42- , NO3-, Si2O3 2- , SiO3 2- , Cl - , F - , S 2- The term "inorganic salt" refers to a compound formed by ionic bonding of elements such as inorganic salts. The compound of a non-metallic element is silicic acid (SiO2) or the like. In the present invention, it is preferable that at least a part of the inorganic particles is a metal salt of calcium, magnesium or barium, or at least a part of the inorganic particles is a metal salt of silicic acid or aluminum, or a metal particle containing titanium, copper, silver, iron, manganese, cerium or zinc.

[0043] The synthesis method of these inorganic particles can be a known method, and may be either a gas-liquid method or a liquid-liquid method. An example of the gas-liquid method is a carbon dioxide gas method, in which magnesium hydroxide is reacted with carbon dioxide gas to synthesize magnesium carbonate. Examples of the liquid-liquid method include a method of reacting an acid (such as hydrochloric acid or sulfuric acid) with a base (such as sodium hydroxide or potassium hydroxide) by neutralization, a method of reacting an inorganic salt with an acid or base, and a method of reacting inorganic salts with each other. For example, barium sulfate can be obtained by reacting barium hydroxide with sulfuric acid, aluminum hydroxide can be obtained by reacting aluminum sulfate with sodium hydroxide, and inorganic particles in which calcium and aluminum are composited can be obtained by reacting calcium carbonate with aluminum sulfate. In addition, when synthesizing inorganic particles in this way, any metal or nonmetallic compound can be made to coexist in the reaction liquid, and in this case, the metal or nonmetallic compound can be efficiently incorporated into the inorganic particles and composited. For example, when calcium phosphate is synthesized by adding phosphoric acid to calcium carbonate, composite particles of calcium phosphate and titanium can be obtained by making titanium dioxide coexist in the reaction liquid.

[0044] (Calcium Carbonate) In the case of synthesizing calcium carbonate, for example, calcium carbonate can be synthesized by the carbon dioxide gas method, the soluble salt reaction method, the lime-soda method, the soda method, etc., and in a preferred embodiment, calcium carbonate is synthesized by the carbon dioxide gas method.

[0045] In general, when calcium carbonate is produced by the carbon dioxide gas method, lime is used as a calcium source, and calcium carbonate is synthesized by a slake process in which quicklime CaO is added with water to obtain slaked lime Ca(OH)2, and a carbonation process in which carbon dioxide CO2 is blown into the slaked lime to obtain calcium carbonate CaCO3. At this time, a suspension of slaked lime prepared by adding water to quicklime may be passed through a screen to remove low-solubility lime particles contained in the suspension. Alternatively, slaked lime may be used directly as a calcium source. In the present invention, when calcium carbonate is synthesized by the carbon dioxide gas method, the carbonation reaction may be carried out in the presence of cavitation bubbles.

[0046] When calcium carbonate is synthesized by the carbon dioxide gas method, the solid content of the aqueous suspension of slaked lime is preferably about 0.1 to 40% by weight, more preferably about 0.5 to 30% by weight, and even more preferably about 1 to 20% by weight. If the solid content is low, the reaction efficiency is low and the production cost is high, and if the solid content is too high, the fluidity is poor and the reaction efficiency is reduced. In the present invention, since calcium carbonate is synthesized in the presence of cavitation bubbles, the reaction liquid and carbon dioxide gas can be suitably mixed even if a suspension (slurry) with a high solid content is used.

[0047] As the aqueous suspension containing slaked lime, one generally used for calcium carbonate synthesis can be used. For example, it can be prepared by mixing slaked lime with water or by slaking (slake) quicklime (calcium oxide) with water. The conditions for slaking are not particularly limited, but for example, the CaO concentration can be 0.05% by weight or more, preferably 1% by weight or more, and the temperature can be 20 to 100°C, preferably 30 to 100°C. The average residence time in the slaking reaction tank (slaker) is also not particularly limited, but can be, for example, 5 minutes to 5 hours, and is preferably within 2 hours. Naturally, the slaker may be of a batch type or a continuous type. In the present invention, the carbonation reaction tank (carbonator) and the slaking reaction tank (slaker) may be separate, or one reaction tank may be used as the carbonation reaction tank and the slaking reaction tank.

[0048] In the synthesis of calcium carbonate, the higher the concentration of raw materials (Ca ions, CO3 ions) in the reaction solution and the higher the temperature conditions, the easier the nucleation reaction proceeds. However, when producing composite fibers, under such conditions, the nuclei are not easily fixed to the cellulose fibers, and inorganic particles free in the suspension are easily synthesized. Therefore, in order to produce composite fibers to which calcium carbonate is firmly bound, it is necessary to appropriately control the nucleation reaction. Specifically, this can be achieved by optimizing the Ca ion and pulp concentrations and slowing down the amount of CO2 supplied per hour. For example, the Ca ion concentration in the reaction vessel is preferably 0.01 mol / L or more and less than 0.20 mol / L. If it is less than 0.01 mol / L, the reaction does not proceed easily, and if it is 0.20 mol / L or more, inorganic particles free in the suspension are easily synthesized. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision of the raw materials with the fibers decreases, so the reaction does not proceed easily, and if it is 4.0% or more, a uniform composite cannot be obtained due to poor stirring. The amount of CO2 supplied per hour is preferably 0.001 mol / min or more and less than 0.060 mol / min per 1 L of reaction solution. If it is less than 0.001 mol / min, the reaction does not proceed easily, and if it is 0.060 mol / min or more, inorganic particles are easily synthesized free in the suspension.

[0049] (Magnesium Carbonate) When synthesizing magnesium carbonate, the method of synthesizing magnesium carbonate can be a known method. For example, magnesium bicarbonate can be synthesized from magnesium hydroxide and carbon dioxide gas, and basic magnesium carbonate can be synthesized from magnesium bicarbonate via magnesium normal carbonate. Magnesium carbonate can be obtained as magnesium bicarbonate, normal magnesium carbonate, basic magnesium carbonate, etc. depending on the synthesis method, but it is particularly preferable that the magnesium carbonate related to the fiber composite of the present invention is basic magnesium carbonate. This is because magnesium bicarbonate has a relatively low stability, and normal magnesium carbonate, which is a columnar (needle) crystal, may be difficult to fix to fibers. On the other hand, by chemically reacting to basic magnesium carbonate in the presence of fibers, a fiber composite of magnesium carbonate and fibers with the fiber surface coated with a scale-like shape can be obtained.

[0050] In the present invention, the reaction liquid in the reaction tank can be circulated. By circulating the reaction liquid in this way and increasing the contact between the reaction liquid and carbon dioxide gas, the reaction efficiency can be increased and the desired inorganic particles can be easily obtained.

[0051] In the present invention, a gas such as carbon dioxide (carbonic acid gas) can be blown into a reaction vessel and mixed with the reaction liquid. According to the present invention, carbonic acid gas can be supplied to the reaction liquid without a gas supply device such as a fan or a blower, and the reaction can be efficiently carried out because the carbonic acid gas is broken down into fine particles by cavitation bubbles.

[0052] In the present invention, the carbon dioxide concentration of the carbon dioxide-containing gas is not particularly limited, but a higher carbon dioxide concentration is preferable. In addition, the amount of carbon dioxide gas introduced into the injector is not limited and can be appropriately selected.

[0053] The carbon dioxide-containing gas of the present invention may be substantially pure carbon dioxide gas or a mixture with other gases. For example, in addition to carbon dioxide gas, a gas containing an inert gas such as air or nitrogen can be used as the carbon dioxide-containing gas. In addition to carbon dioxide gas (carbonic acid gas), the carbon dioxide-containing gas can be suitably used as the carbon dioxide-containing gas, such as exhaust gas discharged from an incinerator, a coal boiler, a heavy oil boiler, or the like in a paper mill. In addition, the carbon dioxide generated from the lime burning process can be used to carry out the carbonation reaction.

[0054] In the synthesis of magnesium carbonate, the higher the concentration of raw materials (Mg ions, CO3 ions) in the reaction solution and the higher the temperature conditions, the easier the nucleation reaction proceeds. However, when producing composite fibers, under such conditions, the nuclei are not easily fixed to the cellulose fibers, and inorganic particles free in the suspension are easily synthesized. Therefore, in order to produce composite fibers to which magnesium carbonate is firmly bound, it is necessary to appropriately control the nucleation reaction. Specifically, this can be achieved by optimizing the Mg ion and pulp concentrations and slowing down the amount of CO2 supplied per hour. For example, the Mg ion concentration in the reaction vessel is preferably 0.0001 mol / L or more and less than 0.20 mol / L. If it is less than 0.0001 mol / L, the reaction does not proceed easily, and if it is 0.20 mol / L or more, inorganic particles free in the suspension are easily synthesized. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the raw materials collide with the fibers less frequently, so the reaction does not proceed smoothly, and if it is 4.0% or more, a homogeneous composite cannot be obtained due to poor mixing. The amount of CO2 supplied per hour should be between 0.001 mol / min and 0.060 mol / min per 1 L of reaction solution. If it is less than 0.001 mol / min, the reaction does not proceed smoothly, and if it is more than 0.060 mol / min, inorganic particles that are free in the suspension are easily synthesized.

[0055] (Barium Sulfate) When synthesized, barium sulfate is an ionic crystalline compound consisting of barium ions and sulfate ions, represented as barium sulfate (BaSO4), which is often in the form of plates or columns and is poorly soluble in water. Pure barium sulfate is a colorless crystal, but when it contains impurities such as iron, manganese, strontium, and calcium, it becomes yellowish brown or blackish gray and translucent. It is obtained as a natural mineral, but can also be synthesized by chemical reactions. In particular, synthetic products obtained by chemical reactions are used for medical purposes (X-ray contrast agents), and are widely used in paints, plastics, storage batteries, etc., taking advantage of their chemically stable properties.

[0056] In the present invention, a composite of barium sulfate and fibers can be produced by synthesizing barium sulfate in a solution in the presence of fibers. For example, a method of reacting an acid (such as sulfuric acid) with a base by neutralization, reacting an inorganic salt with an acid or base, or reacting inorganic salts with each other can be mentioned. For example, barium sulfate can be obtained by reacting barium hydroxide with sulfuric acid or aluminum sulfate, or barium sulfate can be precipitated by adding barium chloride to an aqueous solution containing sulfate.

[0057] In the synthesis of barium sulfate, the higher the concentration of raw materials (Ba ions, SO4 ions) in the solution and the higher the temperature conditions, the easier the nucleation reaction proceeds. However, when producing composite fibers, under such conditions, the nuclei are not easily fixed to the cellulose fibers, and inorganic particles free in the suspension are easily synthesized. Therefore, in order to produce composite fibers to which barium sulfate is firmly bound, it is necessary to appropriately control the nucleation reaction. Specifically, this can be achieved by optimizing the Ba ion and pulp concentrations and slowing down the amount of SO4 ions supplied per hour. For example, the Ba ion concentration in the reaction vessel is preferably 0.01 mol / L or more and less than 0.20 mol / L. If it is less than 0.01 mol / L, the reaction does not proceed easily, and if it is 0.20 mol / L or more, inorganic particles free in the suspension are easily synthesized. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the raw materials collide with the fibers less frequently, so the reaction does not proceed smoothly, and if it is 4.0% or more, a homogeneous composite cannot be obtained due to poor mixing. The amount of SO4 ions supplied per hour is preferably 0.005 mol / min or more and less than 0.080 mol / min per 1 L of reaction solution. If it is less than 0.001 mol / min, the reaction does not proceed smoothly, and if it is 0.080 mol / min or more, inorganic particles that are free in the suspension are easily synthesized.

[0058] (Hydrotalcite) When synthesizing hydrotalcite, the synthesis method of hydrotalcite can be a known method. For example, fibers are immersed in a carbonate aqueous solution containing carbonate ions constituting the intermediate layer and an alkaline solution (such as sodium hydroxide) in a reaction vessel, then an acid solution (a metal salt aqueous solution containing divalent metal ions and trivalent metal ions constituting the basic layer) is added, and the temperature, pH, etc. are controlled to synthesize hydrotalcite by a coprecipitation reaction. Alternatively, fibers can be immersed in an acid solution (a metal salt aqueous solution containing divalent metal ions and trivalent metal ions constituting the basic layer) in a reaction vessel, then an aqueous carbonate solution containing carbonate ions constituting the intermediate layer and an alkaline solution (such as sodium hydroxide) are dropped, and the temperature, pH, etc. are controlled to synthesize hydrotalcite by a coprecipitation reaction. Although a reaction at normal pressure is common, there is also a method of obtaining hydrotalcite by a hydrothermal reaction using an autoclave or the like (JP Patent Publication 60-6619).

[0059] In the present invention, various chlorides, sulfides, nitrates, and sulfates of magnesium, zinc, barium, calcium, iron, copper, cobalt, nickel, and manganese can be used as sources of divalent metal ions constituting the basic layer, and various chlorides, sulfides, nitrates, and sulfates of aluminum, iron, chromium, and gallium can be used as sources of trivalent metal ions constituting the basic layer.

[0060] In the present invention, carbonate ions, nitrate ions, chloride ions, sulfate ions, phosphate ions, etc. can be used as the interlayer anions. When carbonate ions are used as the interlayer anions, sodium carbonate is used as the supply source. However, sodium carbonate can be replaced with a gas containing carbon dioxide (carbonic acid gas), and may be substantially pure carbon dioxide gas or a mixture with other gases. For example, exhaust gas discharged from an incinerator, a coal boiler, a heavy oil boiler, etc. in a paper factory can be suitably used as the carbon dioxide-containing gas. In addition, the carbon dioxide generated from the lime calcination process can be used to carry out the carbonation reaction.

[0061] In the synthesis of hydrotalcite, the higher the concentration of raw materials (metal ions, CO3 ions, etc. that constitute the basic layer) in the solution and the higher the temperature conditions, the easier the nucleation reaction proceeds. However, under such conditions, when producing composite fibers, the nuclei are not easily fixed to the cellulose fibers, and inorganic particles that are free in the suspension are easily synthesized. Therefore, in order to produce composite fibers to which hydrotalcite is firmly bound, it is necessary to appropriately control the nucleation reaction. Specifically, this can be achieved by optimizing the CO3 ion and pulp concentrations and slowing down the amount of metal ions supplied per hour. For example, the CO3 ion concentration in the reaction vessel is preferably 0.01 mol / L or more and less than 0.80 mol / L. If it is less than 0.01 mol / L, the reaction does not proceed easily, and if it is 0.80 mol / L or more, inorganic particles that are free in the suspension are easily synthesized. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision of the raw material with the fiber is reduced, so the reaction does not proceed smoothly, and if it is 4.0% or more, a homogeneous composite cannot be obtained due to poor mixing. The amount of metal ions supplied per hour depends on the type of metal, but for example, in the case of Mg ions, it is desirable to supply 0.001 mol / min or more and less than 0.010 mol / min per 1 L of reaction solution, and more desirably 0.001 mol / min or more and less than 0.005 mol / min. If it is less than 0.001 mol / min, the reaction does not proceed smoothly, and if it is 0.010 mol / min or more, inorganic particles that are free in the suspension are easily synthesized.

[0062] (Alumina / Silica) When synthesizing alumina and / or silica, the synthesis method of alumina and / or silica can be a known method. When one or more of an inorganic acid or an aluminum salt is used as the starting material for the reaction, an alkali silicate is added to synthesize. Although it is also possible to synthesize by using an alkali silicate as the starting material and adding one or more of an inorganic acid or an aluminum salt, the product is better fixed to the fiber when an inorganic acid and / or an aluminum salt is used as the starting material. The inorganic acid is not particularly limited, and for example, sulfuric acid, hydrochloric acid, nitric acid, etc. can be used. Among these, sulfuric acid is particularly preferred in terms of cost and handling. Examples of aluminum salts include aluminum sulfate, aluminum chloride, polyaluminum chloride, alum, potassium alum, etc., and among them, aluminum sulfate can be preferably used. Examples of alkali silicate include sodium silicate or potassium silicate, and sodium silicate is preferred because it is easily available. Any molar ratio of silicic acid to alkali is acceptable, but the one generally available as No. 3 silicic acid has a molar ratio of SiO2:Na2O=about 3 to 3.4:1, and this can be preferably used.

[0063] In the present invention, when producing a composite fiber having silica and / or alumina attached to the fiber surface, it is preferable to synthesize silica and / or alumina on the fiber while maintaining the pH of the reaction solution containing the fiber at 4.6 or less. Although the details of why a composite fiber having a well-coated fiber surface can be obtained in this way are not fully clear, it is believed that maintaining a low pH increases the ionization rate to trivalent aluminum ions, resulting in a composite fiber with a high coverage rate and fixation rate.

[0064] In the synthesis of silica and / or alumina, the higher the concentration of raw materials (silicate ions, aluminum ions) in the reaction solution and the higher the temperature conditions, the more the nucleation reaction proceeds. However, when producing composite fibers, under such conditions, the nuclei are not easily fixed to the cellulose fibers, and inorganic particles that are free in the suspension are easily synthesized. Therefore, in order to produce composite fibers to which silica and / or alumina are firmly bound, it is necessary to appropriately control the nucleation reaction. Specifically, this can be achieved by optimizing the pulp concentration and slowing down the amount of silicate ions and aluminum ions added per hour. For example, the pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision of the raw materials with the fibers decreases, so the reaction does not proceed easily, and if it is 4.0% or more, a uniform composite cannot be obtained due to poor stirring. The supply amount per hour of the added silicate ions and aluminum ions is, for example, in the case of aluminum ions, preferably 0.001 mol / min or more per 1 L of reaction solution, more preferably 0.01 mol / min or more, and more preferably less than 0.5 mol / min, more preferably less than 0.050 mol / min. If it is less than 0.001 mol / min, the reaction does not proceed easily, and if it is 0.050 mol / min or more, inorganic particles are easily synthesized free in the suspension.

[0065] In one preferred embodiment, the average primary particle diameter of the inorganic particles in the composite fiber of the present invention can be, for example, 1.5 μm or less, but the average primary particle diameter can also be 1200 nm or less, 900 nm or less, and even 200 nm or less, 150 nm or less. The average primary particle diameter of the inorganic particles can also be 10 nm or more. The average primary particle diameter can be measured using an electron microscope photograph.

[0066] (Aluminum Hydroxide) Aluminum hydroxide is an ionic crystalline compound consisting of aluminum ions and hydroxide ions, represented by Al(OH)3, and is often in granular form and poorly soluble in water. Products synthesized by chemical reactions are used in medicines and adsorbents, and are also used as flame retardants and fireproofing agents by taking advantage of their property of releasing water when heated.

[0067] In the present invention, a composite of aluminum hydroxide and fibers can be produced by synthesizing aluminum hydroxide in a solution in the presence of fibers. For example, a method of reacting an acid (such as sulfuric acid) with a base by neutralization, reacting an inorganic salt with an acid or base, or reacting inorganic salts with each other can be mentioned. For example, aluminum hydroxide can be obtained by reacting sodium hydroxide with aluminum sulfate, or aluminum hydroxide can be precipitated by adding aluminum chloride to an aqueous solution containing an alkali salt.

[0068] In the synthesis of aluminum hydroxide, the higher the concentration of raw materials (Al ions, OH ions) in the solution and the higher the temperature conditions, the easier the nucleation reaction proceeds. However, when producing composite fibers, under such conditions, the nuclei are not easily fixed to the cellulose fibers, and inorganic particles free in the suspension are easily synthesized. Therefore, in order to produce composite fibers to which aluminum hydroxide is firmly bound, it is necessary to properly control the nucleation reaction. Specifically, this can be achieved by optimizing the OH ion and pulp concentrations and slowing down the amount of Al ions supplied per hour. For example, the OH ion concentration in the reaction vessel is preferably 0.01 mol / L or more and less than 0.50 mol / L. If it is less than 0.01 mol / L, the reaction does not proceed easily, and if it is 0.50 mol / L or more, inorganic particles free in the suspension are easily synthesized. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision of the raw materials with the fibers decreases, so the reaction does not proceed easily, and if it is 4.0% or more, a uniform composite cannot be obtained due to poor stirring. The supply rate of Al ions per hour is preferably 0.001 mol / min or more and less than 0.050 mol / min per 1 L of reaction solution. If it is less than 0.001 mol / min, the reaction does not proceed easily, and if it is 0.050 mol / min or more, inorganic particles are easily synthesized free in the suspension.

[0069] fiber The composite fiber used in the present invention is a composite of fibers such as cellulose fibers and inorganic particles. As the cellulose fibers constituting the composite, for example, natural cellulose fibers as well as regenerated fibers (semi-synthetic fibers) such as rayon and lyocell and synthetic fibers can be used without limitation. Examples of raw materials for cellulose fibers include pulp fibers (wood pulp and non-wood pulp), cellulose nanofibers, bacterial cellulose, animal-derived cellulose such as sea squirts, and algae, and wood pulp can be produced by pulping wood raw materials. Examples of wood raw materials include conifers such as red pine, black pine, Japanese spruce, Sakhalin spruce, Yezo spruce, red pine, larch, fir, hemlock, cedar, cypress, larch, Shirabe, spruce, Japanese cypress, Douglas fir, hemlock, white fir, spruce, balsam fir, cedar, pine, Merkusima pine, and radiata pine, as well as mixtures of these, and broad-leaved trees such as beech, birch, alder, oak, tabu, chinquapin, white birch, cottonwood, poplar, ash, mud willow, eucalyptus, mangrove, lauan, and acacia, as well as mixtures of these.

[0070] The method of pulping natural materials such as wood raw materials (woody raw materials) is not particularly limited, and examples include pulping methods commonly used in the paper manufacturing industry. Wood pulp can be classified by pulping method, and examples include chemical pulp cooked by methods such as the Kraft method, sulfite method, soda method, and polysulfide method; mechanical pulp obtained by pulping using mechanical forces such as a refiner or grinder; semi-chemical pulp obtained by pretreatment with chemicals and then pulping using mechanical forces; waste paper pulp; and deinked pulp. Wood pulp may be in an unbleached state (before bleaching) or in a bleached state (after bleaching).

[0071] Examples of non-wood-derived pulp include cotton, hemp, sisal, Manila hemp, flax, straw, bamboo, bagasse, kenaf, sugarcane, corn, rice straw, paper mulberry, and mitsumata.

[0072] The pulp fibers may be either unbeaten or beaten, and the choice may be made depending on the physical properties of the composite sheet, but it is preferable to beat the pulp fibers, which is expected to improve the sheet strength and promote the fixation of the inorganic particles.

[0073] Furthermore, these cellulose raw materials can be further treated to be used as powdered cellulose, chemically modified cellulose such as oxidized cellulose, and cellulose nanofibers: CNF (microfibrillated cellulose: MFC, TEMPO-oxidized CNF, phosphoric acid esterified CNF, carboxymethylated CNF, mechanically crushed CNF, etc.). As the powdered cellulose used in the present invention, for example, a crystalline cellulose powder having a certain particle size distribution and a rod shape produced by purifying and drying the undecomposed residue obtained after acid hydrolysis of selected pulp, followed by crushing and sieving may be used, or a commercially available product such as KC Flock (Nippon Paper Industries Co., Ltd.), Ceolas (Asahi Kasei Chemicals Co., Ltd.), or Avicel (FMC Co., Ltd.) may be used. The degree of polymerization of cellulose in the powdered cellulose is preferably about 100 to 1500, the degree of crystallinity of the powdered cellulose as measured by an X-ray diffraction method is preferably 70 to 90%, and the volume average particle size as measured by a laser diffraction particle size distribution measuring device is preferably 500 nm or more and 100 μm or less.

[0074] The oxidized cellulose used in the present invention can be obtained by oxidizing in water using an oxidizing agent in the presence of, for example, an N-oxyl compound, and a compound selected from the group consisting of bromides, iodides, or a mixture thereof. The cellulose nanofibers can be produced by defibrating the above-mentioned cellulose raw material. As a defibration method, for example, a method of mechanically grinding or beating an aqueous suspension of cellulose or chemically modified cellulose such as oxidized cellulose using a refiner, a high-pressure homogenizer, a grinder, a single-shaft or multi-shaft kneader, a bead mill, or the like can be used. The cellulose nanofibers may be produced by one or a combination of a plurality of the above methods. The fiber diameter of the produced cellulose nanofibers can be confirmed by observation under an electron microscope, and is preferably in the range of, for example, 5 nm to 300 nm. When producing the cellulose nanofibers, any compound can be further added and reacted with the cellulose nanofibers before and / or after defibrating and / or micronizing the cellulose to produce hydroxyl-modified cellulose nanofibers. The functional groups to be modified include an acetyl group, an ester group, an ether group, a ketone group, a formyl group, a benzoyl group, an acetal, a hemiacetal, an oxime, an isonitrile, an allene, a thiol group, a urea group, a cyano group, a nitro group, an azo group, an aryl group, an aralkyl group, an amino group, an amide group, an imide group, an acryloyl group, a methacryloyl group, a propionyl group, a propioloyl group, a butyryl group, a 2-butyryl group, a pentanoyl group, a hexanoyl group, a heptanoyl group, an octanoyl group, a nonanoyl group, a decanoyl group, an undecanoyl group, a dodecanoyl group, a myristoyl group, a palmitoyl group, a sucrose ... Examples of the alkyl group include acyl groups such as a thearoyl group, a pivaloyl group, a benzoyl group, a naphthoyl group, a nicotinoyl group, a isonicotinoyl group, a furoyl group, and a cinnamoyl group; isocyanate groups such as a 2-methacryloyloxyethylisocyanoyl group; alkyl groups such as a methyl group, an ethyl group, a propyl group, a 2-propyl group, a butyl group, a 2-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a myristyl group, a palmityl group, and a stearyl group; and oxirane groups, oxetane groups, oxyl groups, thiirane groups, and thietane groups.Hydrogen in these substituents may be replaced with functional groups such as hydroxyl groups and carboxy groups. In addition, a part of the alkyl group may be an unsaturated bond. The compound used to introduce these functional groups is not particularly limited, and examples thereof include compounds having a group derived from phosphoric acid, compounds having a group derived from carboxylic acid, compounds having a group derived from sulfuric acid, compounds having a group derived from sulfonic acid, compounds having an alkyl group, and compounds having a group derived from amine. The compound having a phosphoric acid group is not particularly limited, and examples thereof include phosphoric acid, lithium salts of phosphoric acid such as lithium dihydrogen phosphate, dilithium hydrogen phosphate, trilithium phosphate, lithium pyrophosphate, and lithium polyphosphate. Further examples thereof include sodium salts of phosphoric acid such as sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, and sodium polyphosphate. Further examples thereof include potassium salts of phosphoric acid such as potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, and potassium polyphosphate. Further examples thereof include ammonium salts of phosphoric acid such as ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium polyphosphate. Among these, from the viewpoint of high efficiency of phosphoric acid group introduction and easy industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid are preferred, and sodium dihydrogen phosphate and disodium hydrogen phosphate are more preferred, but are not particularly limited. Compounds having a carboxyl group are not particularly limited, but include dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Acid anhydrides of compounds having a carboxyl group are not particularly limited, but include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, and the like. Derivatives of compounds having a carboxyl group are not particularly limited, but include imidized products of acid anhydrides of compounds having a carboxyl group, and derivatives of acid anhydrides of compounds having a carboxyl group.The imide of the acid anhydride of the compound having a carboxyl group is not particularly limited, and includes the imide of a dicarboxylic acid compound such as maleimide, succinimide, and phthalimide. The derivative of the acid anhydride of the compound having a carboxyl group is not particularly limited. For example, at least some of the hydrogen atoms of the acid anhydride of the compound having a carboxyl group, such as dimethylmaleic anhydride, diethylmaleic anhydride, and diphenylmaleic anhydride, are substituted with a substituent (e.g., an alkyl group, a phenyl group, etc.). Among the compounds having a group derived from the above carboxylic acid, maleic anhydride, succinic anhydride, and phthalic anhydride are preferred because they are easily applied industrially and easily gasified, but are not particularly limited. In addition, the cellulose nanofibers may be modified in a form in which the modifying compound is physically adsorbed to the cellulose nanofibers without chemically bonding. Examples of the physically adsorbing compound include surfactants, and any of anionic, cationic, and nonionic surfactants may be used. When the above modification is performed before defibrating and / or pulverizing the cellulose, these functional groups can be eliminated after defibrating and / or pulverizing to return them to the original hydroxyl groups. By applying the above-mentioned modifications, it is possible to promote the defibration of cellulose nanofibers and to make the cellulose nanofibers easier to mix with various substances when they are used.

[0075] The fibers shown above may be used alone or in combination. For example, fibrous materials recovered from wastewater from a paper mill may be fed to the carbonation reaction of the present invention. By feeding such materials to the reaction tank, various composite particles can be synthesized, and fibrous particles can also be synthesized.

[0076] In the present invention, in addition to fibers, substances that can be incorporated into the inorganic particles to produce composite particles can be used. In the present invention, fibers including pulp fibers are used, but it is also possible to produce composite particles in which inorganic particles, organic particles, polymers, etc. are further incorporated by synthesizing inorganic particles in a solution containing these substances.

[0077] The fiber length of the composite fibers is not particularly limited, but for example, the average fiber length can be about 0.1 μm to 15 mm, and may be 1 μm to 12 mm, 100 μm to 10 mm, 400 μm to 8 mm, etc. Among these, in the present invention, the average fiber length is preferably 400 μm or more (0.4 mm or more).

[0078] The average fiber diameter of the composite fibers is not particularly limited, but may be, for example, about 1 nm to 100 μm, and may be 500 nm to 100 μm, 1 μm to 90 μm, 3 μm to 50 μm, 5 μm to 30 μm, etc. Among these, in the present invention, an average fiber diameter of 500 nm or more is preferable because it can improve production efficiency in the post-processing.

[0079] The average fiber length and average fiber diameter of the fibers can be measured by a fiber length measuring device, such as a Valmet Fractionator (manufactured by Valmet).

[0080] The fibers to be composited are preferably used in an amount such that 15% or more of the fiber surface is covered with the inorganic particles. For example, the weight ratio of the fibers to the inorganic particles can be 5 / 95 to 95 / 5, or it can be 10 / 90 to 90 / 10, 20 / 80 to 80 / 20, 30 / 70 to 70 / 30, or 40 / 60 to 60 / 40.

[0081] In a preferred embodiment, the composite fiber according to the present invention has 15% or more of the fiber surface covered with inorganic particles. When the cellulose fiber surface is covered with such an area ratio, the characteristics attributable to the inorganic particles are enhanced, while the characteristics attributable to the fiber surface are reduced.

[0082] The composite fiber according to the present invention can be used in various forms, for example, in the form of powder, pellets, mold, aqueous suspension, paste, sheet, board, block, or other forms. The composite fiber can also be used as a main component together with other materials to form a mold, particle, pellet, or other molded product. There is no particular restriction on the dryer used for drying to obtain a powder, but for example, a flash dryer, band dryer, spray dryer, or the like can be suitably used.

[0083] The composite fiber according to the present invention can be used in various applications, such as paper, fiber, cellulose composite materials, filter materials, paints, plastics and other resins, rubber, elastomers, ceramics, glass, tires, building materials (asphalt, asbestos, cement, boards, concrete, bricks, tiles, plywood, fiberboard, ceiling materials, wall materials, floor materials, roofing materials, etc.), furniture, various carriers (catalyst carriers, pharmaceutical carriers, agricultural chemical carriers, microorganism carriers, etc.), adsorbents (impurity removal, deodorization, dehumidification, etc.), antibacterial agents, antiviral agents, wrinkle prevention agents, clay, abrasives, friction materials, modifiers, repair materials, insulation materials, heat-resistant materials, heat dissipation materials, moisture-proof materials, water-repellent materials, water-resistant materials, light-shielding materials, sealants, shielding materials, insect repellents, adhesives, medical materials, paste materials, discoloration prevention agents, radio wave absorbing materials, insulating materials, sound-proofing materials, interior materials, vibration-proofing materials, semiconductor sealing materials, radiation shielding materials, materials, etc. It can also be used as various fillers and coating agents in the above applications. Among these, adsorbents, antibacterial materials, antiviral agents, friction materials, radiation shielding materials, flame retardant materials, building materials, and heat insulating materials are preferred.

[0084] The composite fiber of the present invention may be applied to papermaking applications, such as printing paper, newspaper, inkjet paper, PPC paper, kraft paper, fine paper, coated paper, lightly coated paper, wrapping paper, tissue paper, colored fine paper, cast coated paper, non-carbon paper, label paper, thermal paper, various fancy papers, water-soluble paper, release paper, process paper, wallpaper base paper, flame retardant paper (non-combustible paper), laminated board base paper, printed electronics paper, battery separator, cushion paper, tracing paper, impregnated paper, ODP paper, building material paper, decorative paper, envelope paper, tape paper, heat exchange paper, synthetic fiber paper, sterilized paper, waterproof paper, oil-resistant paper, heat-resistant paper, photocatalytic paper, decorative paper (grease removal paper, etc.), various sanitary papers (toilet paper, tissue paper, wipers, diapers, sanitary products, etc.), tobacco paper, paperboard (liner, core base paper, white paperboard, etc.), paper plate base paper, cup base paper, baking paper, abrasive paper, synthetic paper, etc. That is, according to the present invention, a composite of inorganic particles and fibers having a small primary particle size and a narrow particle size distribution can be obtained, and therefore the composite can exhibit properties different from those of conventional inorganic fillers having particle sizes of more than 2 μm. Furthermore, unlike the case where inorganic particles are simply blended with fibers, when inorganic particles are combined with fibers, not only are the inorganic particles more easily retained in a sheet, but also a sheet can be obtained in which the inorganic particles are uniformly dispersed without agglomeration. In a preferred embodiment, it has been revealed from the results of electron microscope observation that the inorganic particles in the present invention are not only fixed on the outer surface and inside the lumen of the fiber, but also formed inside the microfibrils.

[0085] In addition, when using the composite fiber according to the present invention, particles generally called inorganic fillers and organic fillers, and various fibers can be used in combination. For example, examples of inorganic fillers include calcium carbonate (light calcium carbonate, heavy calcium carbonate), magnesium carbonate, barium carbonate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, clay (kaolin, calcined kaolin, delami kaolin), talc, zinc oxide, zinc stearate, titanium dioxide, silica produced from sodium silicate and mineral acid (white carbon, silica / calcium carbonate complex, silica / titanium dioxide complex), white clay, bentonite, diatomaceous earth, calcium sulfate, zeolite, inorganic fillers that regenerate and utilize ash obtained from the deinking process, and inorganic fillers that form complexes with silica or calcium carbonate during the regeneration process. As the calcium carbonate-silica complex, in addition to calcium carbonate and / or light calcium carbonate-silica complex, amorphous silica such as white carbon may be used in combination. Examples of organic fillers include urea-formaldehyde resin, polystyrene resin, phenolic resin, micro hollow particles, acrylamide complex, wood-derived substances (fine fibers, microfibril fibers, powdered kenaf), modified insolubilized starch, and ungelatinized starch. Fibers can be used without restriction, including natural fibers such as cellulose, synthetic fibers artificially synthesized from raw materials such as petroleum, regenerated fibers (semi-synthetic fibers) such as rayon and lyocell, and inorganic fibers. In addition to the above, natural fibers include protein-based fibers such as wool, silk thread, and collagen fibers, and complex carbohydrate-based fibers such as chitin / chitosan fibers and alginic acid fibers. Examples of cellulose-based raw materials include pulp fibers (wood pulp and non-wood pulp), bacterial cellulose, cellulose derived from animals such as sea squirts, and algae. Wood pulp can be produced by pulping wood raw materials.Examples of wood raw materials include conifers such as red pine, black pine, Japanese spruce, spruce, red pine, larch, fir, hemlock, cedar, cypress, larch, Shirabe, spruce, hiba, Douglas fir, hemlock, white fir, spruce, balsam fir, cedar, pine, Merkushima pine, radiata pine, and mixtures thereof, and broad-leaved trees such as beech, birch, alder, oak, tabu, chinquapin, white birch, cottonwood, poplar, ash, Japanese knotweed, eucalyptus, mangrove, lauan, acacia, and mixtures thereof. The method for pulping the wood raw material is not particularly limited, and examples include pulping methods commonly used in the paper manufacturing industry. Wood pulp can be classified according to the pulping method, and examples of such pulp include chemical pulp digested by methods such as the Kraft method, the sulfite method, the soda method, and the polysulfide method; mechanical pulp obtained by mechanical pulping using a refiner, grinder, or the like; semi-chemical pulp obtained by mechanical pulping after chemical pretreatment; waste paper pulp; and deinked pulp. Wood pulp may be in an unbleached state (before bleaching) or in a bleached state (after bleaching). Examples of non-wood-derived pulp include cotton, hemp, sisal, Manila hemp, flax, straw, bamboo, bagasse, kenaf, sugarcane, corn, rice straw, paper mulberry, and mitsumata. Wood pulp and non-wood pulp may be either unbeaten or beaten. Furthermore, these cellulose raw materials can be further processed to be used as powdered cellulose, chemically modified cellulose such as oxidized cellulose, and cellulose nanofibers: CNF (microfibrillated cellulose: MFC, TEMPO-oxidized CNF, phosphate-esterified CNF, carboxymethylated CNF, mechanically crushed CNF). Examples of synthetic fibers include polyester, polyamide, polyolefin, and acrylic fibers, while examples of semi-synthetic fibers include rayon and acetate. Examples of inorganic fibers include glass fibers, carbon fibers, and various metal fibers. These may be used alone or in combination of two or more types.

[0086] The average particle size, shape, etc. of the inorganic particles constituting the composite fiber of the present invention can be confirmed by observation with an electron microscope. Furthermore, by adjusting the conditions for synthesizing the inorganic particles, inorganic particles having various sizes and shapes can be composited with the fiber. EXAMPLES

[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to such examples. In addition, unless otherwise specified in this specification, concentrations, parts, etc. are based on weight, and numerical ranges are described as including their endpoints.

[0088] Experiment 1: Synthesis and evaluation of composite fibers 1-1. Zinc-based hydrotalcite and fiber composite fiber (samples a and b) Solutions were prepared for the synthesis of hydrotalcite (Zn-based HT). A mixed aqueous solution of Na2CO3 (Fujifilm Wako Pure Chemicals) and NaOH (Fujifilm Wako Pure Chemicals) was prepared as an alkaline solution (solution A). A mixed aqueous solution of ZnSO4 (Fujifilm Wako Pure Chemicals) and Al2(SO4)3·16H2O (Fujifilm Wako Pure Chemicals) was prepared as an acid solution (solution B). Alkaline solution (solution A, Na2CO3 concentration: 0.05M, NaOH concentration: 0.8M) ·Acid solution (B solution, Zn-based, ZnSO4 concentration: 0.9M, Al2(SO4)3·16H2O concentration: 0.15M)

[0089] Cellulose fibers were used as the composite fiber. Specifically, the pulp fibers used were made of bleached hardwood kraft pulp (LBKP, Nippon Paper Industries, fiber width 20 μm) and bleached softwood kraft pulp (NBKP, Nippon Paper Industries, fiber width 50 μm) in a weight ratio of 8:2, and had their Canadian standard freeness adjusted to 300 ml using a single disc refiner (SDR).

[0090] An alkaline solution was added to the pulp fibers to prepare an aqueous suspension containing pulp fibers (pulp fiber concentration: 3.0%, pH: about 12.8). This aqueous suspension (pulp solid content 20 kg) was placed in a 1000 L reaction vessel, and while stirring the aqueous suspension, an acid solution was added dropwise to synthesize a composite fiber of hydrotalcite microparticles and fibers. Using an apparatus such as that shown in Figure 1, the reaction temperature was 50°C, and the dropwise addition was stopped when the pH of the reaction solution reached about 7.5. After the dropwise addition was completed, the reaction solution was stirred for 30 minutes to mature. The sample after the maturation was dehydrated in a centrifugal dehydrator, and 2 to 10 times the amount of water was added, and the dehydration was repeated until the electrical conductivity was 100 mS / m or less, and the composite fiber was washed.

[0091] 1-2. Barium sulfate and fiber composite fiber (sample c) As with sample a, pulp fibers with a Canadian standard freeness adjusted to 300 ml (LBKP:NBKP=8:2) were used.

[0092] Barium hydroxide octahydrate (FUJIFILM Wako Pure Chemical Industries, Ltd.) was added to the pulp fibers to prepare an aqueous suspension containing pulp fibers (pulp fiber concentration: 3.0%, pH: about 12.5). This aqueous suspension (pulp solid content 20 kg) was placed in a 1000 L reaction vessel, and while stirring the aqueous suspension, sulfuric acid (FUJIFILM Wako Pure Chemical Industries, prepared as a 2% aqueous solution) was dropped to synthesize a composite of barium sulfate microparticles and fibers. Using an apparatus such as that shown in Figure 1, the reaction temperature was 50°C, and the drop was stopped when the pH of the reaction solution reached about 7.5. After the drop was completed, the reaction solution was stirred for 30 minutes, and then washed with 10 times the amount of water to remove salt. Next, the composite fiber was dehydrated using a centrifugal dehydrator, and 2 to 10 times the amount of water was added, and the dehydration was repeated until the electrical conductivity was 100 mS / m or less, to wash the composite fiber.

[0093] 1-3. Composite fiber of copper-containing zinc-based hydrotalcite and fiber (sample d) As with sample a, pulp fibers with a Canadian standard freeness adjusted to 300 ml (LBKP:NBKP=8:2) were used.

[0094] To synthesize copper-containing zinc-based hydrotalcite (Cu-containing Zn-based HT), a mixed aqueous solution of Na2CO3 (Fujifilm Wako Pure Chemicals) and NaOH (Fujifilm Wako Pure Chemicals) was prepared as an alkaline solution (solution A). In addition, a mixed aqueous solution of three chemicals, ZnSO4 (Fujifilm Wako Pure Chemicals), CuSO4 (Wako Pure Chemicals), and Al2(SO4)3·16H2O (Fujifilm Wako Pure Chemicals), was prepared as an acid solution (solution C). Alkaline solution (solution A, Na2CO3 concentration: 0.05M, NaOH concentration: 0.8M) ·Acid solution (C solution, ZnSO4 concentration: 0.75M, CuSO4 concentration: 0.15M, Al2(SO4)3 16H2O concentration: 0.15M) Except for using the above chemicals, composite fibers were synthesized in the same manner as for sample a, and the sample after aging was dehydrated in a centrifugal dehydrator to wash the composite fibers.

[0095] 1-4. Composite fiber of copper-containing zinc-based hydrotalcite and PET fiber (sample e) A composite fiber was synthesized in the same manner as sample d, except that polyethylene terephthalate fiber (PET, fiber diameter: 1.7 decitex, fiber length: 5 mm) was used as the fiber. After aging, the sample was dehydrated in a centrifugal dehydrator and the composite fiber was washed.

[0096] 1-5. Composite fiber of titanium oxide, magnesium hydrotalcite, and fiber (sample f) As with sample a, pulp fibers with a Canadian standard freeness adjusted to 300 ml (LBKP:NBKP=8:2) were used.

[0097] To synthesize magnesium hydrotalcite (Mg-HT), a mixed aqueous solution of MgSO4 (Fujifilm Wako Pure Chemical Industries, Ltd.) and Al2(SO4)3·16H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) was prepared as an alkaline solution (solution A) and an acid solution (solution D). Alkaline solution (solution A, Na2CO3 concentration: 0.15M, NaOH concentration: 2.4M) ·Acid solution (D solution, MgSO4 concentration: 0.9M, Al2(SO4)3·16H2O concentration: 0.15M)

[0098] Pulp fiber was added to the alkaline solution to prepare an aqueous suspension containing pulp fiber (pulp fiber concentration: 2.0%, pH: about 12.7). 3.5 kg of titanium dioxide (R-3L, manufactured by Sakai Chemical Industry Co., Ltd.) was added to this aqueous suspension (pulp solid content 3 kg) and thoroughly stirred. While stirring this aqueous suspension, an acid solution was dropped, the reaction temperature was set to 50°C, and the dropping was stopped when the pH of the reaction solution became about 7. After the dropping was completed, the reaction solution was stirred for 30 minutes, and then washed with 10 times the amount of water to remove salt. Next, the composite fiber was dehydrated in a centrifugal dehydrator, and 2 to 10 times the amount of water was added, and the dehydration was repeated until the electrical conductivity became 100 mS / m or less, to wash the composite fiber.

[0099] 1-6. Evaluation of composite fibers The bicomponent fiber samples were evaluated according to the following procedure. (1)Surface coverage The obtained composite fibers were observed under an electron microscope (Sample a: Figure 2, Sample b: Figure 3, Sample c: Figure 4, Sample d: Figure 5, Sample f: Figure 6). In each sample, approximately 70% of the fiber surface was covered with inorganic particles. (2) Moisture content (moisture rate) The sample was dried at 105°C for 2 hours, and the moisture content was calculated from the weight lost by drying. The solid content (concentration) is "100 - moisture content". (3) Weight ratio of fibers to inorganic particles For the sample dried at 105°C for 2 hours, the ash content of the composite fiber was measured based on JIS P 8251:2003, and the weight ratio of the fiber and inorganic particles constituting the composite fiber was calculated.

[0100] [Table 1]

[0101] Experiment 2: Production and evaluation of granules containing bicomponent fibers 2-1. Manufacturing of granules containing composite fibers (Sample 1) Granules were manufactured using sample a as the raw material. Specifically, sample a (moisture content: about 70%) was placed in a Plosser mixer (WB type, Pacific Machinery Works) and stirred at room temperature. Next, steam was introduced into the Plosser mixer to raise the temperature inside the device to 80°C or higher, and the mixture was dried while stirring. After drying until the moisture content reached about 10%, water was added and the mixture was granulated (finished particle size after granulation: about 0.5 mm, moisture content after granulation: about 50%). Granules with a particle size of 0.5 mm or less were finally obtained using a 0.5 mesh sieve. (Sample 2) Except for using sample b as the raw material, granulation was carried out in the same manner as sample 1. Using a 0.5 to 1.0 mesh sieve, granules of 0.5 to 1.0 mm were finally obtained. (Sample 3) The granules of Sample 2 were air dried for 72 hours to produce granules with a moisture content of 20%. (Sample 4) Granules were produced in the same manner as for Sample 3, except that Sample a was used as the raw material. (Sample 5) Sample b was used as a raw material, and granulation was carried out in the same manner as sample 2, except that the final particle size after granulation was set to 1.0 mm. Using a 1.0-3.0 mesh sieve, granules with particle sizes of 1.0-3.0 mm were finally obtained. (Sample 6) The granules of Sample 5 were air dried for 72 hours to produce granules with a moisture content of 20%. (Sample 7) Granules were produced in the same manner as for Sample 5, except that Sample a was used as the raw material. (Sample 8) Sample b was used as a raw material, and granulation was carried out in the same manner as sample 3, except that the final particle size after granulation was set to 3.0 mm. Using a 3.0-4.0 mesh sieve, granules with particle sizes of 3.0-4.0 mm were finally obtained. (Sample 9) Sample b (moisture content: about 70%) was dried until the moisture content was 10% or less, and then further refined to a size of about 0.5 mm or less using a cutter mill. The processed sample was added to a rolling granulator (CF-360N, Freund Corporation) and granulated while adding water (finished particle size after granulation: about 1.0 mm, moisture content after granulation: about 20%). Granules with a particle size of 1.0 to 3.0 mm were finally obtained using a 1.0 to 3.0 mesh sieve. (Sample 10) It was produced in the same manner as sample 3, except that sample c was used as the raw material. (Sample 11) It was produced in the same manner as sample 2, except that sample d was used as the raw material. (Sample 12) It was produced in the same manner as sample 2, except that sample e was used as the raw material. (Sample 13) It was produced in the same manner as sample 2, except that sample f was used as the raw material. (Sample 14: Comparative Example) The moisture content of sample b was adjusted to approximately 70% using a Büchner funnel to prepare a sample. (Sample 15: Comparative Example) Water was added to 100 g of powdered cellulose (product name: W-50, Nippon Paper Industries, average particle size: 40 μm) and mixed with stirring, and the wet powder (moisture content: about 5%) was granulated using a rolling granulator while adding water (finished particle size after granulation: about 1 mm, moisture content after granulation: about 35%). The obtained granules were sieved to obtain granules with a particle size of 0.5 to 1.0 mm.

[0102] 2-2.Evaluation of granules The samples were evaluated according to the following evaluation procedures. (1) Moisture content (moisture content), weight percentage of inorganic matter The moisture content (%) was measured in the same manner as in Experiment 1. The weight ratio (%) of the inorganic content was also calculated by measuring the weight ratio of the fibers to the inorganic particles in the same manner as in Experiment 1.

[0103] (2) Angle of repose (fluidity) Using a powder property measuring instrument (Hosokawa Micron, Powder Tester PT-X type), a powder sample was dropped from the attached metal funnel (φ5 mm) at a vibration scale of 1.5, and the ridge angle of the peak formed by the powder was measured using the angle measurement method "Peak Operation" to obtain the angle of repose. If the angle of repose was measurable, it was evaluated as "fluidity present," and if it was not measurable, it was evaluated as "no fluidity." In addition, the lower the angle of repose value, the better the fluidity.

[0104] (3) Dispersibility 90g of sodium chloride and 10g of sample were added to a plastic bag (170mm x 240mm) and mixed manually for 3 minutes. 10g of the mixture was taken, 200ml of distilled water was added, and the sodium chloride was dissolved using a stirrer. The treated solution was filtered using filter paper (JIS P3801, for quantitative analysis, type 5B), and the residue on the filter paper was dried under tension at 50°C for 2 hours, and the weight of the granules contained in 10g of the mixture was measured. The dispersion rate was calculated based on the formula "weight of granules after drying / 1g x 100", and a value of 70% or more was considered to be a pass (○), and a value of less than 70% was considered to be a fail (×).

[0105] (4) Bulk density The mass of a sample lightly packed in a certain volume was measured and divided by the volume to obtain the "bulk density (loose bulk density)". Specifically, the mass of a sample was measured when it was packed in a 1000 mL graduated cylinder up to the 1000 mL mark, and the bulk density (g / cm 3 ) values ​​were calculated.

[0106] (5) Particle size distribution A laser diffraction particle size distribution measuring device (Mastersizer 3000, manufactured by Malvern Panalytical) was used. The cumulative 50% particle size (average particle size) by volume was obtained from the sample (0.3 to 1.0 g) used for the measurement.

[0107] [Table 2]

[0108] As is clear from the above table, the granules of the present invention had better flowability and dispersibility than those not processed into granules.

Claims

1. Granules containing composite fibers of fibers and inorganic particles, having a particle size of 0.1 to 10 mm and a moisture content of less than 60%.

2. The granules according to claim 1, having an angle of repose of 30 to 58°.

3. 3. Granules according to claim 1 or 2, wherein the inorganic particles comprise metal salts of calcium, magnesium, barium or aluminium, metal particles comprising titanium, copper or zinc, or silicates.

4. The granules according to any one of claims 1 to 3, wherein the inorganic particles are hydrotalcite.

5. The granule according to any one of claims 1 to 4, wherein the weight ratio of inorganic particles in the granule is 10% or more.

6. A granule according to any one of claims 1 to 5, wherein the fibres are cellulose fibres.

7. The granule according to any one of claims 1 to 6, wherein 15% or more of the fiber surface is covered with inorganic particles.

8. A method for producing the granules according to any one of claims 1 to 7, comprising the steps of: A step of synthesizing inorganic particles in a liquid containing fibers to obtain composite fibers; A step of granulating the composite fibers into granules having a particle size of 0.1 to 10 mm; The above method.

9. The method according to claim 8 , wherein in the granulating step, the composite fibers are granulated while being dried.

10. The method according to claim 8, wherein the moisture content of the composite fiber is reduced to less than 60% before granulation.

11. The method according to claim 8, wherein the bicomponent fibers are micronized before being granulated.

Citation Information

Patent Citations

  • Papermaking method using fiber filler composite

    JP2004502048A

  • Manufacturing method of fine fibrous cellulose-containing article

    JP2017057285A

  • Complex of fiber and inorganic particle

    JP2018090939A

  • Composite of fiber and inorganic particles

    WO2018097312A1

  • Titanium oxide composite fibers and method for producing same

    WO2019087694A1